Melatonin, a possible promising panacea for premature ovarian failure - Guo, Ting; Gu, Chao; Li, Bin (Menopause Review/Przegląd Menopauzalny, 2011)
Premature ovarian failure (POF) is characterized by impairment of ovarian function unrelated to elevated follicle-stimulating hormone (FSH) before the age of 40. The consequence of POF is severe and distinctive, presenting from infertility to symptoms caused by hormone deprivation. The mechanism of POF remains unclear and current treatments are therefore ineffective. Melatonin (N-acetyl-5-methoxytryptamine) is a neuroendocrinal hormone chiefly secreted by the pineal body. Melatonin exerts extensive physiological and pharmacological effects on the biological rhythm, oxidative stress, reproduction, autoimmune and tumourigenesis. However, current researches have not yet brought melatonin into the study of POF. In the present review, we have involved state-of-the-art research progress of melatonin in ovary with regard to oxidation, follicle formation and function, and ovarian autoimmune disorders since these aspects mainly dispose to POF development. The features that melatonin scavenges reactive oxygen species (ROS), directly and indirectly induces follicle maturation, ovulation and inhibits apoptosis, and modulates autoimmune derangements in the ovaries are highly indicative that melatonin can effect in combating POF. Also, in this respect we have discussed the possibility of applying melatonin in the treatment of POF and have listed evidence of studies in vitro and in vivo . Vacant research directions are subsequently suggested and the future application of melatonin in POF treatment is prospected.